Blood and Lymph Node Dissemination of Clonal Genome-Intact Human Immunodeficiency Virus 1 DNA Sequences During Suppressive Antiretroviral Therapy. (1st April 2020) - Kuo, Hsiao-Hsuan; Banga, Riddhima; Lee, Guinevere Q; Gao, Ce; Cavassini, Matthias; Corpataux, Jean-Marc; Blackmer, Jane E; zur Wiesch, Schulze; Yu, Xu G; Pantaleo, Giuseppe; Perreau, Matthieu; Lichterfeld, Mathias
Abstract: The majority of cells with latent human immunodeficiency virus 1 infection are located in lymphoid tissues that are difficult to access. In the current study, we used single-genome near-full-length proviral sequencing to evaluate intact and defective proviruses in blood and lymph node CD4 T cells enriched for specific functional polarizations. We observed minor variations between the frequencies of proviral sequences within individual CD4 T-cell subsets and across tissue compartments. However, we noted multiple clonal clusters of identical intact or defective proviral sequences from distinct compartments and CD4 T-cell subpopulations, suggesting frequent interchanges between viral reservoir cells in blood and tissues. Abstract : Using single-genome, near-full-length viral sequencing, we showed that clonal clusters of intact and defective human immunodeficiency virus 1 DNA sequences from patients receiving antiretroviral treatment patients consist of mixed proviral species from blood and lymph nodes.